Contradictions of Transnational Trash Trade Regulations in Indonesia - Safrian Hamzah; Mochammad Tanzil Multazam (Indonesian Journal of Law and Economics Review, 2019)
This study aims to examine the contradictory regulation regarding trade of waste in indonesia. Principle what is described in Article 69 paragraph (1) letter C Law no. 32 of 2009 concerning Environmental Protection and Management which states that everyone is prohibited from entering waste originating from outside the Republic of Indonesia into the territory of the Republic of Indonesia. Based on the principle of lex superior derogate legi inferior, there are contradictory arrangements. Then the Minister of Trade Regulation No. 84 of 2019 concerning Provisions for the Import of Non Hazardous and Toxic Wastes as Industrial Raw Materials in conjunction with the Minister of Trade Regulation No. 92 of 2019 concerning Amendments to the Minister of Trade Regulation No. 84 of 2019 potentially for a judicial review. Regulation is needed that doesn’t neglect the environment to support the economy. But also doesn’t hinder the economy for focus on the environment. The point is that the existence of rules that bridge the interests of humans and the environment is the best solution so that their existence is maintained.